Effect of anthropization on macroinvertebrate communities in the Kou River, Burkina Faso. - Souleymane, Sanogo; Inoussa, Compaore; Boureima, Sawadogo; Blaise, Ouedraogo Raogo; Bilassé, Zongo; Bismarck, Nacro Hassan (International Journal of Environment, Agriculture and Biotechnology, 2021)
The structuring of aquatic macroinvertebrate communities is used as an indicator of the effects of human activities on river ecosystems. This study focused on the distribution of macroinvertebrate communities along the Kou River in western Burkina Faso. Its objective was to characterize macroinvertebrate communities and water quality in the Kou River protected-site-manipulated site continuum in order to develop biological indicators for monitoring and assessing the overall health of aquatic ecosystems. Macroinvertebrate sampling, carried out using a cloud net and a Suber net, was carried out during the low-water period from January to April 2018. Their identification was carried out using a binocular magnifying glass and reference determination keys, and was limited to the systematic Family level. The study identified 04 Classes, 14 Orders and 54 Families of macroinvertebrates. The analysis of these results showed that 100% of the identified Orders and 98.15% of the identified Families were found in the protected site, compared to 64.29% of the Orders and 59.26% of the Families in the anthropized site. It also showed that the protected site is taxonomically richer than the anthropized site with the presence of 53 Families (98.15% of the Families identified), compared to 32 Families representing 59.26% of the Families identified for the anthropized site. Also, 22 taxa are specific to the protected site and remain absent in the anthropized site. This study also allowed the identification of 04 potential taxa bioindicators that would constitute excellent biological tools for monitoring aquatic systems. The agro-demographic pressure on natural resources has a negative impact on the diversity of species, the dynamics of which must be better monitored. The extension of the tools tested in the present study to river managers will strengthen their technical capacity for monitoring surface water quality.